Reliability of Nodule Size and Fine Needle Aspiration Cytology in Diagnosis of Thyroid Malignancy (The Insight, 2022)
Introduction: Thyroid nodules are one of the commonest thyroid problems in the world. The importance of size of solitary thyroid nodule lies in the significant risk of malignancy and is known to be an important prognostic factor. Fine-needle aspiration cytology (FNAC) is a highly sensitive and specific test for evaluation of thyroid nodule. Though FNAC is a safe, rapid, cost-effective diagnostic tool for evaluation of thyroid nodules, sometimes it cannot differentiate between benign and malignant disease. This study will find out the role of nodule size as a simple predictor associated with thyroid malignancy and will also provide diagnostic significances of FNAC in diagnosing thyroid nodule. Methods: This observational study carried out in the department of General surgery and Otolaryngology, Combined Military Hospital, Dhaka and Dhaka Medical College Hospital from Nov 2015 to April 2016. 100 patients who underwent thyroidectomy for nodular goiters were included in this study. Nodule size was measured by USG and fine needle aspiration of nodules performed. Histological data of patients were used to estimate the actual nodule size. Predictive role of nodule size and diagnostic significance of FNAC was evaluated by comparison with histopathology. Result: Total 100 patients were enrolled (M/F= 24/76) with mean age 42 (±11.3) and 39.3 (±11.4) years among benign and malignant cases respectively. Mean nodule size was larger for malignant than benign nodules (2.8 vs 2.2 cm). Risk of malignancy was foundsignificant among larger nodule (≥2 cm) in comparison to smaller nodule (01– 1.9 cm) (32.5% vs 10%, p= 0.004). Out of 100 nodules, 62 (62%) solid, 11 (11%) cystic and 27 (27%) were mixed in nature. Increase in nodule size was associated with lowerproportion of papillary carcinoma and higher proportion of follicular or other carcinoma. FNAC was done in all 100 patients. Among them 68 were benign and 12 were cellular follicular lesion. Malignancy was found among 11 patients and the remaining 09 were suspicious for malignancy. Histopathologically 81 patients were diagnosed as benign. Among them 63 nodular goiter, 10 follicular adenoma, and 08 were thyroiditis. The remaining 19 patients were malignant which comprises 15 papillary carcinoma, 03follicular carcinoma and 01 anaplastic carcinoma. Altogether 80 benign, 11 malignant and 09 suspicious cases were confirmed by cytologically. After histopathology 05 of 09 suspicious cases and 03 of 80 benign cases were found malignant. FNAC showed 93%accuracy, 84.21% sensitivity, 95.1% specificity with positive predictive value (PPV) 80% and negative predictive value (NPV) 96.3%. Conclusion: Risk of thyroid malignancy has been found significant among larger nodule (≥2 cm) in comparison to smaller nodule.FNAC is a highly sensitive, specific, and accurate initial diagnostic test for evaluation of thyroid malignancy.
Keywords: Nodule Size; FNAC; Thyroid Malignancy; Diagnosis